The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/bjh.16592
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of older patients with primary central nervous system lymphoma treated in routine clinical practice in the UK: methotrexate dose intensity correlates with response and survival

Abstract: Summary Data on older patients with primary central nervous system lymphoma (PCNSL) are scarce. Comorbidities and performance status frequently compromise outcomes in this group. Medical records for consecutive patients ≥65 years (n = 244) with PCNSL diagnosed 2012–2017 from 14 UK centres were retrospectively reviewed. Of these 192 patients received methotrexate (MTX)‐based treatment. Patients were categorised based on clinician's treatment choice into ‘palliative’ (n = 52), ‘less intensive: MTX ± rituximab ± … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 31 publications
7
39
0
Order By: Relevance
“…Still, treatment of these patients with MTX‐based regimens in clinical routine seems to be feasible and results in favorable outcomes in a relevant proportion of these patients. In fact, another report suggests that higher dose intensity of MTX is a major contributor to favorable outcomes 28 . Patients receiving a median amount of 10,6 g/m 2 MTX showed two‐year overall survival of 50% compared to 24% in patients receiving a median amount of 8,8 g/m 2 MTX 28 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, treatment of these patients with MTX‐based regimens in clinical routine seems to be feasible and results in favorable outcomes in a relevant proportion of these patients. In fact, another report suggests that higher dose intensity of MTX is a major contributor to favorable outcomes 28 . Patients receiving a median amount of 10,6 g/m 2 MTX showed two‐year overall survival of 50% compared to 24% in patients receiving a median amount of 8,8 g/m 2 MTX 28 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, another report suggests that higher dose intensity of MTX is a major contributor to favorable outcomes 28 . Patients receiving a median amount of 10,6 g/m 2 MTX showed two‐year overall survival of 50% compared to 24% in patients receiving a median amount of 8,8 g/m 2 MTX 28 . However, poor performance status and high‐risk profile might contribute to reduced MTX dosing and poor outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, the prognosis for PCNSL has been dismal. Nevertheless, in recent years, several studies have reported considerable progress in treatment outcomes [9][10][11][12][13]29]. For example, in the International Extranodal Lymphoma Study Group-32 (IELSG-32), the 30-month progression-free survival rate in the group treated with MATRix regimen (methotrexate, cytarabine, thiotepa, and rituximab) was 49%, compared with 23% of those treated with methotrexate-cytarabine alone and 30% of those treated with methotrexate-cytarabine plus rituximab [11].…”
Section: Prognosismentioning
confidence: 99%
“…The prognosis for PCNSL has been poor, but several clinical trials with relatively short follow-up times have reported considerable progress in treatment outcomes among selected clinical trial populations [9][10][11][12][13]. However, this is in contrast to most of the population-based reports, which have demonstrated only minor improvement in long-term survival [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 96%
“…It responds poorly to conventional chemotherapy, and the overall 5-year survival rate is only about 33% [5]. Combination chemotherapy with high-dose methotrexate, whole brain radiotherapy, and autologous hematopoietic stem cell transplantation can bene t PCNSL patients [6][7][8][9]. In recent years, novel targeted therapeutics have been emerging as potential treatments for PCNSL [10].…”
Section: Systematic Review Registration Prospero Crd42020218143mentioning
confidence: 99%